Doping-control of excitons and magnetism in few-layer CrSBr - Farsane Tabataba-Vakili; Huy P. G. Nguyen; Anna Rupp; Kseniia Mosina; Anastasios Papavasileiou; Kenji Watanabe; Takashi Taniguchi; Patrick Maletinsky; Mikhail M. Glazov; Zdenek Sofer; Anvar S. Baimuratov; Alexander Högele (Nature Communications)
Abstract Magnetism in two-dimensional materials reveals phenomena distinct from bulk magnetic crystals, with sensitivity to charge doping and electric fields in monolayer and bilayer van der Waals magnet CrI3. Within the class of layered magnets, semiconducting CrSBr stands out by featuring stability under ambient conditions, correlating excitons with magnetic order and thus providing strong magnon-exciton coupling, and exhibiting peculiar magneto-optics of exciton-polaritons. Here, we demonstrate that both exciton and magnetic transitions in bilayer and trilayer CrSBr are sensitive to voltage-controlled field-effect charging, exhibiting bound exciton-charge complexes and doping-induced metamagnetic transitions. Moreover, we demonstrate how these unique properties enable optical probes of local magnetic order, visualizing magnetic domains of competing phases across metamagnetic transitions induced by magnetic field or electrostatic doping. Our work identifies few-layer CrSBr as a rich platform for exploring collaborative effects of charge, optical excitations, and magnetism.